Analisis Pelaksanaan TRIAS Program Usaha Kesehatan Sekolah di SMK Negeri Kota Bengkulu - Supangat, Exsa Akhirullah; Kosvianti, Emi; Oktavidiati, Eva; Ramon, Agus (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2025)
Background : The School Health Business Program (UKS) is the formation of the mindset of students who are accustomed to clean and healthy living behavior. This research aims to find out how the UKS Trias Program is implemented at SMK N 1 Bengkulu City. Metodh:The type of research used is qualitative with a descriptive approach. namely research that attempts to describe the object or subject being studied according to what it is. The informants in this research were informants related to the implementation of UKS Trias at SMK N 1 Bengkulu City. Result: The results of research on Health Education have been carried out well leading to the Trias UKS guidebook with counseling and training carried out. Health services have been implemented including disease prevention activities, healthy environmental development has been implemented through school environmental cleanliness activities such as class pickets. The Healthy Environment Development Program at SMK N 1 Bengkulu City is in accordance with the UKS Trias, such as fulfilling infrastructure, increasing socialization or health education. Conclusion: Suggestions for schools and educational institutions to use as evaluation material for the TRIAS UKS program include providing outreach Keywords: Vocational School, Trias UKS, Students, Health, Evaluation